EFFECT OF OPEN-ENDED APPROACH TOWARD CRITICAL THINKING ABILITY OF VOCATIONAL HIGH SCHOOL STUDENTS - Sakti, Debra Pratama (TRIADIK, 2016)
Abstract: This study aimed to determine the effect of open-ended approach toward the critical thinking ability of Mathematical of students in Vocational High School. Type of study is an experimental study with a quasi-experimental design were implemented in SMK N 1 Central Bengkulu in the first semester of the school year 2016/2017 the study population was all students of Class X and Class X sample is ATP-2 as the experimental class and Class X-ATP 1 as the control class. The results showed that there are significant open-ended approach to the critical thinking ability of mathematical (p<0,05). In addition, based on the value of rsquare , open-ended approach gives considerable influence equal to 30.8% on the students critical thinking skills mathematically.